Semantic Approach for Al-Quran Knowledge Representation in Islamic Knowledge Management Framework - Ta'a, Azman; Shaari@Hj Ashari, Muhammad Shakirin; Che Mohamed Arif, Ahmad Suki; Abu Bakar, Muhamad Shahbani; Mahmad, Muhamad Amar (Journal of Quranic Sciences and Research, 2021)
Using ontology data model to accurately represent Al-Quran knowledge using its inherent structure of Division (Juz), Chapter (Surah), and Verse (Ayah) should be done within the framework of the Islamic Knowledge Management (IKM). Data modelling neglecting the IKM framework would result in inaccuracy and irrelevant result in knowledge processing activities involving the Al-Quran. Many of the current approaches utilizing conventional knowledge management methods such as taxonomy, hierarchy, or tree structure are limited in the sense that they only define the concepts of knowledge without relating it to a theme that defined from corpus of Islamic knowledge. In the case of Al-Quran, a classification of themes from background knowledge are important to provide a structural explanation of the knowledge and to ensure that the results obtained from a searching function of the corpus of the knowledge will result in an accurate and appropriate meaning intended by the Islamic knowledge. The aims of this paper is to demonstrate the construction of Al-Quran ontology and elaborate the searching method for representing and retrieving the relevance and accurate verses toward the theme of Al-Quran by using the semantic-based approach. The specification of Al-Quran ontology of which the prototype application was built on has been validated by experts. The evaluation test of the Al-Quran ontology application furthermore shows high precision result from searching functions done. With a good level of accuracy achieved from the test, it is hopeful that Al-Quran ontology application will provide a new experience of Al-Quran themes searching and browsing within the IKM framework for the Al-Quran readers. A capability to efficiently and accurately performing search of Al-Quran will certainly improve their understanding of Al-Quran contents.